Mitigating fading effects for mobile communications - Balaji, Srinivasan (2018)
This project is aimed at analyzing fading mitigation techniques in wireless communication system. Multipath fading is simulated and observed under different wireless fading channel environments. Performance comparison parameters like signal-to-noise ratio (SNR), bit error rate (BER) etc. are calculated and analyzed. Mitigation using diversity combining techniques is then analyzed and implemented in these fading environments. Some of the diversity combining techniques used are selection combining, maximal ratio combining and equal gain combining. The improvements in performance parameters are then observed and plotted. The result is that maximal ratio combining has better performance than the other techniques. Furthermore, advanced mitigation techniques like the hybrid diversity technique is also studied. The performance parameters are explained theoretically for these advanced mitigation techniques and used for future analysis.